ANALISIS PEMAHAMAN SENI BUDAYA MELAYU MAHASISWA PGSD FKIP UNIVERSITAS RIAU - Engla Afria Denci; Zufriady; Zariul Antosa (STKIP Subang, 2026)
This research aims to describe the understanding of Malay cultural arts among PGSD FKIP students at Riau University. The type of research conducted is a survey using a descriptive quantitative approach. The population for this study comprises 472 PGSD FKIP students from Riau University, cohort 2020-2024. The sample was drawn using simple random sampling techniques. The data collection method employed in this study is a non-test technique in the form of a questionnaire. The obtained data were summarized and concluded based on five indicators. The data analysis technique utilized is descriptive statistical analysis. Based on the analysis of the data, the students' responses per indicator are as follows: for the Knowledge Indicator, the average score is 70.33, categorized as high; for the Understanding of Values and Norms Indicator, the average is 74.02, also categorized as high; for the Experience and Behavior Indicator, the average is 65.58, categorized as adequate; for the Understanding of Symbolism and Meaning Indicator, the average is 71.91, classified as high; and for the Understanding of Social and Cultural Contexts Indicator, the average is the highest at 75.82, categorized as high. According to the data obtained from the research, it indicates that PGSD FKIP students at Riau University for the cohort 2020-2024 achieved an overall average score of 71.53. Thus, it can be concluded that the understanding of Malay cultural arts among PGSD FKIP students at Riau University for the cohort 2020-2024 falls within the